2023
DOI: 10.1039/d2ta07453b
|View full text |Cite
|
Sign up to set email alerts
|

Polymer composites with hierarchical architecture and dielectric particles for efficient daytime subambient radiative cooling

Abstract: Passive daytime radiative cooling (PDRC) is an emerging energy-free cooling technology, which can weaken our dependence on air-conditioning requirements with energy-consuming. Though the advance in photonic micro/nanostructures PDRC materials achieves...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Conventional approaches to prepare the radiative cooling materials usually depend on combinations of multiple materials or, when utilizing a single material, complicated techniques such as phase inversion or sacrificial templates . In contrast, electrospinning technology stands out for its inherent advantages, enabling precise control over process parameters and a straightforward procedure. , Especially, for the fabrication of stretchable membranes, electrospinning techniques usually employ thermoplastic polymers such as PU and SBS to prepare the nanofiber structure through a single nozzle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional approaches to prepare the radiative cooling materials usually depend on combinations of multiple materials or, when utilizing a single material, complicated techniques such as phase inversion or sacrificial templates . In contrast, electrospinning technology stands out for its inherent advantages, enabling precise control over process parameters and a straightforward procedure. , Especially, for the fabrication of stretchable membranes, electrospinning techniques usually employ thermoplastic polymers such as PU and SBS to prepare the nanofiber structure through a single nozzle.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional approaches to prepare the radiative cooling materials usually depend on combinations of multiple materials 27 or, when utilizing a single material, complicated techniques such as phase inversion 28 or sacrificial templates. 29 In contrast, electrospinning technology stands out for its inherent advantages, enabling precise control over process parameters and a straightforward procedure.…”
Section: T H I S C O N T E N T I S O N L Y L I C E N S E D F O R C O ...mentioning
confidence: 99%
“…PDRC surfaces reect sunlight and dissipate heat to outer space by emitting electromagnetic waves through an atmospheric transparent window (8-13 mm), which require zero energy input, 4,5 and hence have signicant potential for energyefficient buildings, 6,7 photovoltaic cooling, 8 and personal thermal management. [9][10][11] A range of materials have been proposed for PDRC applications, including polymer lms, [12][13][14][15] nano-coating materials, [16][17][18][19] and photonic structural materials. 20,21 For instance, Mandal et al introduced a phase inversion-based method for fabricating hierarchically porous poly(vinylidene uoride-co-hexauoropropene) [P(VdF-HFP) HP ] coatings with excellent PDRC capability; 22 Bao et al demonstrated a highly scalable nanoparticle-based double-layer coating (a top reective layer with high solar albedo and a bottom emissive layer of TiO 2 , SiO 2 , and SiC nanoparticles) to achieve efficient terrestrial radiative cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Ideal passive all-day radiative cooling (PARC) films require specific materials with high emissivity in the atmospheric window (8–13 μm), such as metal oxides, semiconductors, and polymers, as well as designing of precise structures to achieve a high reflectivity in the solar spectrum range (0.3–2.5 μm), minimizing the absorption of solar energy. Compared with dielectric-based photonic structural materials, , fiber membranes, , and other composite materials, hierarchical pores that enable Mie scattering can scatter solar light; such pores can be easily manufactured and are cost-effective and scalable. , Effective scattering of the entire solar spectrum can be achieved by rationally adjusting the size and distribution of these pores . Recent studies have demonstrated that the nonsolvent-induced phase separation (NIPS) method is effective for fabricating porous structures in polymer films, such as polyvinylidene fluoride–hexafluoropropylene (PVDF–HFP), polydimethylsiloxane, , cellulose acetate (CA), , and polylactic acid (PLA) films for PARC. For instance, Mandal et al developed a cost-effective and scalable porous radiative cooler by utilizing PVDF–HFP, acetone (ACE), and water as raw materials.…”
Section: Introductionmentioning
confidence: 99%